The Mineralogy, Geochemistry and Origin of the Supergene Manganese Occurrences in the Southern Minas Gerais, Brazil - Parrotti, Davi Diorio [UNESP] (2023)
In equatorial and tropical regions, supergene mineral deposits created during water/rock interactions are found. Simply put, these supergene deposits are formed through the accumulation of low solubility ions or through the preservation of primary minerals. The supergene manganese (Mn) deposits are examples of the economic importance associated with the chemical weathering processes. In Brazil, the Southern Brasilia Orogen (SBO) was generated during the collision between the Paranapanema Craton and the passive margin of the São Francisco Craton. In the southern Minas Gerais (MG), several supergene Mn occurrences are hosted in the SBO, which were originated during the chemical weathering of gondites belonging to the Amparo Complex. Here, we studied the supergene Mn occurrences in the southern MG, more specifically in the municipalities of Ouro Fino and Careaçu. The MnO contents ranged from 25.50 to 28.40 wt% at Ouro Fino and from 16.80 to 21.20 wt% at Careaçu. These supergene Mn deposits have a diverse mineral assemblage, being composed of spessartine, quartz, Mn-oxides, goethite and kaolinite. The various Mn minerals formed due to spessartine incongruent dissolution were hollandites, cryptomelanes, romanechites, pyrolusites and lithiophorites. Both study areas are relevant for the possible opening of mines for the commercialization of Mn.